Surfactant modified glassy carbon electrode as an efficient sensing platform for the detection of Cd (ӏӏ) and Hg (ӏӏ). (1st May 2017) - Zahid, Anum; Shah, Afzal; Iftikhar, Faiza Jan; Shah, Aamir Hassan; Qureshi, Rumana
Abstract: A highly sensitive electrochemical sensor using a novel surfactant 1-cyclohexyl-3-dodecanoylthiourea (CDT) as a recognition layer was developed for the detection of Cd 2+ and Hg 2+ using electrochemical impedance spectroscopy, chronocoulometry and a number of voltammetric techniques such as cyclic, square wave and differential pulse stripping voltammetry. For optimization, the effect of several experimental factors such as concentration of the surfactant, scan rate, pH, accumulation time, number of cycles and supporting electrolytes were investigated. The limits of detection quite lower than the danger level suggested by world health organization (WHO), Environmental protection agency (EPA) and European water quality (EWQ) suggested the suitability of our designed sensor for monitoring metal based water toxins. Theoretical studies carried out for the calculation of interaction energy of CDT with Hg 2+ and Cd 2+ supported the experimental findings. The validity of the proposed method for real water sample analysis was ensured from reasonable percentage recoveries and less than 4% RSD values. Moreover, the designed sensor demonstrated excellent discrimination ability for the target analytes in the presence of interfering agents.